A Brief History of the Encoding of Hand Position by the Cerebral Cortex: Implications for Motor Control and Cognition. (24th January 2018) - Battaglia-Mayer, Alexandra
Abstract: Encoding hand position by the cerebral cortex is essential not only for the neural representation of the body image but also for different actions based on eye–hand coordination. These include reaching for visual objects as well as complex movement sequences, such as tea-making, tool use, and object construction, among many others. All these functions depend on a continuous refreshing of the hand position representation, relying on both predictive signaling and afferent information. The hand position influence on neural activity in the parietofrontal system, together with eye position signals, are the basic elements of an eye–hand matrix from which all the above functions can emerge and could be regarded as key features of a network with several entry points, command nodes and outflow pathways, as confirmed by the discovery of a direct parietospinal projection for the control of hand action. The integrity of this system is crucial for daily life, as testified by the consequences of cortical lesions, spanning from severe paralysis to complex forms of apraxia. In this review, I will sketch my personal understanding of the scientific and conceptual trajectory of a line of investigation with many unexpected influences on cortical function and disease, from motor behavior to cognition.